AB0493 Association between antiviral igm antibodies and myositis autoantibodies in patients with autoimmune myositis in bulgarian population. (23rd January 2014) - Kalinova, D.; Todorova, E.; Kyurkchiev, D.; Rashkov, R.
Abstract : Background: Considerable evidences indicate that the viruses may be important environmental factors in the pathogenesis of the connective tissue diseases – systemic lupus erythematodes, systemic sclerosis, myositis, etc. 1 Viruses activate a humoral immune response, characterized by an early rise of antigen-specific IgM antibodies (Abs), and cellular immune response by activating antigen-specific T lymphocytes. Cytotoxic lymphocytes release granzyme B/perforin, which modify self proteins. Modified proteins become immunogenetic and induce the synthesis of autoantibodies (aAbs). 2 Autoimmune myositis (AIM) is a syndrome, characterized by involvement of the cellular and humoral immune systems in skeletal muscle pathology, response to immunotherapies and the presence of aAbs – myositis-specific (MSAs) and myositis-associated (MAAs) aAbs. 3 Objectives: The objective of this study was to determine prevalence of antibodies (Abs) IgM against some viruses, respectively the presence of a viral infection, and to analyse association between antiviral Abs and MSAs, MAAs aAbs in a group of patients with AIM in Bulgarian population. Methods: Sera were collected from 37 patients with myositis as diagnoses were determined using Bohan and Peter classification (1975) and 30 health controls, after informed written consent. Sera were tested by enzyme linked immunosorbent assay for Abs IgM against Influenza A and B, Parainfluenza, Coxsackie virus, cytomegalovirus, Epstein-barr virus, Parvovirus and HIV. MSAa and MAAs were determined by Immunoblot test and enzyme linked immunosorbent assay. Chi-square analysis, Fisher's exact test was used for to ascertain the association between antiviral Abs and myositis aAbs, as p value didn't exceed 0.05. Results: Antibodies IgM against some viruses were present in 45% of patients with AIM and in 19% in controls (p=0.028). It was observed Abs against Influenza A and B, Parainfluenza, Coxsackie virus, EBV and CMV in patients with myositis. It wasn't found statistically significance in comparing frequency of the separate antiviral Abs between group of patients and control group (p > 0.05). MSAs and MAAs were expressed in 62% of patients with positive antiviral Abs. It was determined statistically significant difference between a group with antiviral Abs + myositis aAbs and a group with antiviral Abs – myositis aAbs (p=0.031). The most common myositis aAbs were anti-Ro52 (16%), anti-dsDNA (8%), anti-Jo-1 (5%), anti-Ro60 (5%). Other aAbs were detected in less patients with myositis. Conclusions: Virus infections can induce autoimmune response by various mechanisms including molecular mimicry, epitope spreading, release of cryptic epitopes, and expression of "neoantigens", which are accompanied by production of aAbs. 1 The results in our study suggest the role of viruses in etiopathogenesis of AIM. References: Fujinami RS, et al. Molecular mimicry bystander activation, or viral persistence infections and autoimmune disease. Clin Microbiol Rev, 2006, 19: 80-94. Lundberg I: Inflammatory muscle disease - etiology and pathogenesis (myositis). Rheumatology, ELSEVIER, Toronto, Canada, 2011: 1457-1469. Troyanov Y, et al. Novel classification of idiopathic inflammatory myopathies based on overlap syndrome features and autoantibodies. Medicine, 2005, 84: 231-249. Disclosure of Interest: None Declared